Analysis of Cell–Cell Bridges in Haloferax volcanii Using Electron Cryo-Tomography Reveal a Continuous Cytoplasm and S-Layer - Sivabalasarma, Shamphavi; Wetzel, Hanna; Nußbaum, Phillip; van der Does, Chris; Beeby, Morgan; Albers, Sonja-Verena (Frontiers in Microbiology, 2021)
Halophilic archaea exchange DNA and proteins using a fusion-based mating mechanism. Scanning electron microscopy previously suggested that mating involves an intermediate state, where cells are connected by an intercellular bridge. To better understand this process, we used electron cryo-tomography and fluorescence microscopy to visualize cells forming these intercellular bridges. Electron cryo-tomography showed that the observed bridges were enveloped by an S-layer and connected mating cells via a continuous cytoplasm. Macromolecular complexes like ribosomes and unknown thin filamentous helical structures were visualized in the cytoplasm inside the bridges, demonstrating that these bridges can facilitate exchange of cellular components. We followed formation of a cell-cell bridge by fluorescence time-lapse microscopy between cells at a distance of 1.5 µm. These results shed light on the process of haloarchaeal mating and highlight further mechanistic questions.